The Influence of Using Word Search Puzzle on The Vocabulary Mastery of Eighth Grade Students at SMP 25 Bengkulu City - Amelia, Tri Puja; Susanto, Ferri; Revola, Yashori (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the effect of using the Word Search Puzzle as a learning medium on the vocabulary mastery of eighth-grade students at SMP Negeri 25 Bengkulu City. This research is motivated by the low level of students’ vocabulary mastery due to less engaging teaching methods and the limited use of interactive learning media. This study employed a quantitative method with a quasi-experimental design (nonequivalent control group design). The population consisted of all eighth-grade students, with the sample taken from two classes, namely the experimental and control groups, each consisting of 28 students. The research procedure included a pre-test, followed by treatment in the experimental group using Word Search Puzzle, while the control group was taught using conventional methods, and concluded with a post-test. The data obtained were analyzed using statistical tests with the help of SPSS version 27. The results showed a significant improvement in the experimental group compared to the control group. The mean score of the experimental group increased from 55.8 to 84.9, while the control group increased from 49.7 to 72.5. These findings were supported by the results of the t-test, where t-count > t-table (6.390 > 2.005) with a significance value of < 0.001 < 0.05, indicating that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It can be concluded that the Word Search Puzzle has a significant effect on students’ vocabulary mastery, with a contribution of 0.431 (43.1%). This media has the potential to be an innovative and effective alternative for increasing English vocabulary mastery among junior high school students.